“The West of the Orient”: The Depiction of the Ottoman Capital in Persian Hajj Travelogues - YILDIZ, GÜLLÜ (De Gruyter, 2022)
Comparing modernization processes in the Ottoman Empire and the Persian Empire, and assuming a similar pattern of development for these two empires are very common in historical and cultural studies.¹ During the second half of the nineteenth century, the period covered by the corpus considered in the present study, the two empires were struggling against the threat from European states and putting all their efforts into technical improvements and political transformation, as they both faced military, economic, and political pressure. This was the direct result of the adaptation and replication of modern Western models within these societies. The more contacts they had with Western civilization, the more they experienced an irrevocable transformation at home. However, the Ottoman Empire surpassed Iran in terms of the time and intensity of their connection with Europe. In most cases, it was an important channel for the transfer of Western ideas and innovations and served for a long time as a gateway to Europe.²